OP0041 Tocilizumab (TCZ) in Combination and Monotherapy Versus Methotrexate (MTX) in MTX-Naive Patients (PTS) with Early Rheumatoid Arthritis (RA): Clinical and Radiographic Outcomes from a Randomised, Placebo-Controlled Trial. (23rd January 2014) - Burmester, G.; Rigby, W.; van Vollenhoven, R.; Kay, J.; Rubbert-Roth, A.; Kelman, A.; Dimonaco, S.; Mitchell, N.
Abstract : Background: Recent recommendations support intensive treatment of pts with early RA to achieve remission or low disease activity. 1 -3 TCZ was not previously studied exclusively in an early RA population. Objectives: To assess the efficacy and safety of treatment with TCZ ± MTX versus MTX in MTX-naive pts with early RA (defined as ≤2 y since diagnosis). Methods: Pts were randomised 1:1:1:1 (double-dummy, double-blind) to receive TCZ 8 mg/kg (TCZ8) + MTX (primary intervention), TCZ8 monotherapy, TCZ 4 mg/kg (TCZ4) + MTX or MTX for 104 wks. Pts received IV TCZ q4w, and MTX starting at 7.5 mg qw, escalating to 20 mg qw by wk 8. Inclusion criteria included RA for ≤2 y, DAS28 >3.2, MTX naive, elevated ESR or CRP and presence of RF or anti-CCP antibodies or radiographic erosion(s). Primary endpoint was proportion of pts achieving DAS28 remission (DAS28–ESR <2.6) at 24 wks. Key secondary endpoints included mean changes from baseline (BL) to wk 52 in van der Heijde modified Total Sharp Score (mTSS) and improvement in physical function (using HAQ-DI). A hierarchy of statistical testing was implemented to control the type 1 error rate for multiplicity. This trial is ongoing; 52-wk data are reported here. Results: The intent-to-treat (ITT) population consisted of 1157 pts. BL characteristics were similar in all treatment groups: mean RA duration, 0.4-0.5 y; mean DAS28, 6.6-6.7; mTSS, 5.66-7.72. Statistically significantly greater proportions of TCZ8 + MTX than MTX pts achieved DAS28 remission and ACR20/50/70 responses at wks 24 and 52 (p<0.05); statistically significant improvements in mean mTSS and HAQ-DI were also observed at wk 52 (p<0.05; Table). TCZ8 monotherapy also met the primary endpoint (p<0.05). Both TCZ8 monotherapy and TCZ4 + MTX showed numerically greater improvements versus MTX across key secondary endpoints. Observed adverse events (AEs) with TCZ were consistent with its known safety profile. Incidences of AEs and serious AEs were similar across treatment groups, while serious infections were highest in pts on combination therapy (Table). Overall, 9 deaths were observed across all treatment groups; the underlying causes of death were variable. Image/graph: Conclusions: TCZ was effective as combination therapy and monotherapy in MTX-naive pts with early active RA. TCZ treatment resulted in improvements from BL in signs, symptoms and physical function and in inhibition of structural joint damage in all treatment groups. Of the 3 TCZ treatment groups, efficacy responses for TCZ versus MTX were consistently greatest in the TCZ8 + MTX group. The overall safety of TCZ was consistent with its known profile. References: Arthritis Care Res 2012;64:625; Ann Rheum Dis 2010;69:631; Ann Rheum Dis 2010;69:964 Disclosure of Interest: G. Burmester Grant/research support from: Abbott, BMS, Pfizer, Roche, UCB, Consultant for: Abbott, BMS, MedImmune, MSD, Pfizer, Roche, UCB, Speakers bureau: Abbott, BMS, MSD, Pfizer, Roche, UCB, W. Rigby Consultant for: Roche, R. van Vollenhoven Grant/research support from: Abbott, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: Abbott, BMS, GSK, MSD, Pfizer, Roche, UCB, J. Kay Grant/research support from: [paid to UMass Med School] Abbott, Ardea, Lilly, Fidia Farmacutici, Roche, Sanofi Aventis, Consultant for: Amgen, Baxter, BMS, Celgene, fourteen22, Genentech, Hospira, Horizon, Janssen, Medac Pharma, Molecular Partners, PanGenetics, Pfizer, Roche, Savient, UCB, A. Rubbert-Roth Grant/research support from: Roche, Chugai, Pfizer, Consultant for: Roche, Chugai, Pfizer, UCB, MSD, Speakers bureau: Roche, UCB, MSD, A. Kelman Employee of: Genentech, a member of the Roche group, S. Dimonaco Employee of: Roche, N. Mitchell Employee of: Roche